Percutaneous Dissolution of Gallstones using Methyl Tert-Butyl Ether - Johnson L Thistle; Bert T Petersen; Claire E Bender; Andrew J Leroy; Timothy M Ridgway (Canadian Journal of Gastroenterology)
Radiolucent cholesterol gallstones can be dissolved rapidly by methyl terc-buryl ether (MTBE) introduced directly into the gallbladder. Percutaneous transhepatic catheter placement is a well established interventional radiology procedure and is the preferred route for MTBE administration. A small number of patients have been treated using nasobiliary placement of a gallbladder catheter. Rapid stirring automatic pump systems allow dissolution of most cholesterol stones, but some may require extracorporeal shock wave lithotripsy to achieve complete dissolution and aspiration of debris. Large bore percutaneous fragmentation and extraction methods require general anesthesia but are applicable to pigment stones.